Tratamento por adsorção em bagaço de laranja de um efluente da indústria têxtil - Ströher, Ana Paula (2010)
The great diversity of industrial activities textile occasions, during the production process, the generation of effluent with characteristics quite complex, varying according to the type of manufacturing process used. In Brazil, the textile sector has a big importance in the national and regional economy. Nevertheless, by consuming considerables quantities of water and synthetics dyes, the sector creates big quantities of colored effluent. This is possible because of the presence of dyes that do not fix in the fibers during the dyeing process. Adsorption is one of the techniques that has been used with success for the effective removal of dyes. However, the efficiency of the adsorption process depends on the choice of a proper adsorbent. Because of the high cost of some conventional adsorbent, researches have been directed to the use of alternative adsorbent, such as orange pulp. In this study was investigated the efficiency of adsorption in orange peel of a textile effluent, combined with a pre-treatment of ultra / microfiltration. This step pretreatment was necessary, since initial tests showed that there was no adsorption process in the raw effluent. In this way, the pre-treatment effluent separated components that were inhibiting the adsorption. It was performed the characterization the effluent before and after each step of the treatment of effluent, determining pH, color, turbidity, volatile and suspended solids, DQO and DBO. The pre-treatment was carried out with ceramic membranes of sizes 0.01, 0.1 and 0.8 micrometers. The working pressure used in this case was 3 bar and temperature of the effluent of 30 °C. The adsorption step was made in batch. For the use of the adsorbent, the pulp was thawed, washed and dried in a convective dryer at a temperature of 42 °C and air flow rate of 1.3 m/s. Next, was featured in granulometric particle sizes of 0.5 mm. The effluent was adjusted to pH 3, which presented a higher removal of compounds by the orange peel. The equilibrium time was calculated at 50 hours, a relatively high. The isotherm models studied were the Langmuir and Freundlich. The process variables of the model isotherms were estimated using the computational package for nonlinear estimation software STATISTICA® 6.0 using the method of estimation Quasi-Newton. and the best fit for the isotherms was the model of Freundlich. The adsorption step significantly reduced color and turbidity, however increased the parameters of DQO, DBO and solids in relation to the previous step because it is an adsorbent with organic matter and rapidly degraded. At the end of the combination of steps and comparing with the raw effluent, it showed a reduction of all parameters studied, but according to the CONAMA resolution 357, the effluent after treatment does not meet the standards for release on bodies receptors.